2018
DOI: 10.17059/2018-3-24
|View full text |Cite
|
Sign up to set email alerts
|

Does Agriculture Matter for Economic Growth of Uttar Pradesh (India)?

Abstract: Twenty-five years have passed since economic reform in India. It brought about many macroeconomic policy changes in the economy. Although these policy changes helped the manufacturing and services sector to grow, agriculture did not get any direct benefits from economic reforms. It was assumed that it would get indirect benefits due to changes in exchange and trade policy, liberal industrial licensing system and reduction in industrial protection, which would benefit tradable agriculture by ending discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…e literature [7] proposed a new type of multivariable early warning model. is kind of multivariable early warning model can make in-process analysis during the Lehman crisis or help postcrisis financial decision-making, and is of great benefit to the financial crisis of the entire country.…”
Section: Related Workmentioning
confidence: 99%
“…e literature [7] proposed a new type of multivariable early warning model. is kind of multivariable early warning model can make in-process analysis during the Lehman crisis or help postcrisis financial decision-making, and is of great benefit to the financial crisis of the entire country.…”
Section: Related Workmentioning
confidence: 99%
“…rough behavioral research on consumers' online shopping process, determine which factors are affected by consumers in the process of consumer behavior, increase the driving force of positive factors, and eliminate negative factors, so as to maximize the satisfaction of consumer needs and then achieve the purpose of marketing, that is, to obtain consumer recognition, so as to obtain greater benefits [4]. Combining with the rise of social e-commerce model and the penetration rate of various social software applications, on this basis, research on many e-commerce models, conduct research on consumer online shopping behaviors of characteristic agricultural products under the social e-commerce model, and discuss the influencing factors of consumers' online shopping of characteristic agricultural products are of very important practical significance [5]. Under the social e-commerce model, research on the behavior of consumers to purchase characteristic agricultural products online through social software will help small farmers, retail suppliers, and agricultural products enterprises to optimize the marketing strategies of characteristic agricultural products, improve their deficiencies, and attract more consumers.…”
Section: Related Workmentioning
confidence: 99%
“…The hypotheses of this study were proposed based on the tenets of the Kuznets theory. [19] studied the contribution of agriculture to economic growth in Uttar Pradesh, India. The study employed a long-run cointegrating analysis and found that agricultural development drives economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%